2004
DOI: 10.2334/josnusd.46.25
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the clinical effects of systemic and local doxycycline in the treatment of chronic periodontitis

Abstract: In this study, the clinical efficacies of systemic doxycycline (SD) and local doxycycline (LD) in the treatment of chronic periodontitis were compared. Forty-five patients were studied in 3 main groups with 5 treatments: SD alone, SD+scaling-root planing (SD+SRP), LD alone, LD+SRP and SRP alone. Antibiotic-treated patients were given doxycycline treatment alone in 1 quadrant of their upper jaws, and doxycycline+SRP was given in the contralateral quadrant. The areas included at least 4 teeth with ≥ 5 mm pockets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(91 reference statements)
2
15
0
2
Order By: Relevance
“…Bu özelliklerinden dolayı enflamasyonla birlikle olan akne vulgaris ve rozaseada düşük dozlarda iyileştirici etkileri gösterilmiştir. Üstelik, 1998 yılında ilk kez düşük doz doksisiklin (20 mg), erişkin periodontit tedavisi için Amerikan İlaç ve Gıda Dairesi (FDA) tarafından onaylanmıştır [16][17][18] . Ayrıca diğer anti-enflamatuvar etkiden sorumlu mekanizma ise, matriks metalloproteinaz (MMP) enzimlerini inhibe etmeleridir ve buna bağlı olarak pek çok enflamatuvar hastalık, yara iyileşmesi, embriyogenez, tümör invazyonu ve anjiyogenez gibi olayları etkilemeleridir.…”
Section: Anti-enflamatuvar Etkiunclassified
“…Bu özelliklerinden dolayı enflamasyonla birlikle olan akne vulgaris ve rozaseada düşük dozlarda iyileştirici etkileri gösterilmiştir. Üstelik, 1998 yılında ilk kez düşük doz doksisiklin (20 mg), erişkin periodontit tedavisi için Amerikan İlaç ve Gıda Dairesi (FDA) tarafından onaylanmıştır [16][17][18] . Ayrıca diğer anti-enflamatuvar etkiden sorumlu mekanizma ise, matriks metalloproteinaz (MMP) enzimlerini inhibe etmeleridir ve buna bağlı olarak pek çok enflamatuvar hastalık, yara iyileşmesi, embriyogenez, tümör invazyonu ve anjiyogenez gibi olayları etkilemeleridir.…”
Section: Anti-enflamatuvar Etkiunclassified
“…The association of an antibiotic with a slow-releasing drug delivery system may facilitate the maintenance of effective therapeutic concentrations at the application site for longer periods. In addition, the risks of adverse drug reactions and the development of bacterial resistance are reduced [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SRP with adjunct antibiotic therapy is usually performed, which helps in the extermination of pathogenic microbes from infected periodontal pockets [24,25]. In the study by Akalın et al [24], clinical effi cacies of locally delivered and systemically delivered doxycycline were compared as adjuncts to conventional SRP in the treatment of periodontal disease. The results demonstrated that locally delivered or systemically delivered doxycycline when used as adjuncts to SRP are equally eff ective in the treatment of periodontal disease [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Akalın et al [24], clinical effi cacies of locally delivered and systemically delivered doxycycline were compared as adjuncts to conventional SRP in the treatment of periodontal disease. The results demonstrated that locally delivered or systemically delivered doxycycline when used as adjuncts to SRP are equally eff ective in the treatment of periodontal disease [24]. It was therefore hypothesized that SRP when performed with adjunct antibiotic therapy is more eff ective in reducing periodontal infl ammation and hyperglycemia as compared to when SRP is used as a sole therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%